2008
DOI: 10.1262/jrd.20024
|View full text |Cite
|
Sign up to set email alerts
|

Paraventricular .ALPHA.1- and .ALPHA.2-Adrenergic Receptors Mediate Hindbrain Lipoprivation-induced Suppression of Luteinizing Hormone Pulses in Female Rats

Abstract: Abstract. Acute central lipoprivation suppresses pulsatile luteinizing hormone (LH) release and increases blood glucose levels through noradrenergic input to the hypothalamic paraventricular nucleus (PVN) in female rats. The present study was conducted to identify adrenergic receptor subtypes involved in central lipoprivation-induced suppression of pulsatile LH secretion and increases in plasma glucose levels in female rats. Acute hindbrain lipoprivation was produced by injection into the fourth cerebroventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Glucose sensing by the hindbrain is thought to be of particular importance in suppression of LH secretion under negative energy balance [4,5]. It is also possible that other oxidizable fuels, such as fatty acids [6,7] and ketone bodies [8], serve as metabolic signals informing the brain of nutritional conditions to induce LH suppression.Ketone bodies are produced in the liver from excess amounts of acetyl-CoA under malnutritional conditions. Under such circumstances, glucose utilization in the brain decreases, while uptake of ketone bodies into the brain increases [9][10][11].…”
mentioning
confidence: 99%
“…Glucose sensing by the hindbrain is thought to be of particular importance in suppression of LH secretion under negative energy balance [4,5]. It is also possible that other oxidizable fuels, such as fatty acids [6,7] and ketone bodies [8], serve as metabolic signals informing the brain of nutritional conditions to induce LH suppression.Ketone bodies are produced in the liver from excess amounts of acetyl-CoA under malnutritional conditions. Under such circumstances, glucose utilization in the brain decreases, while uptake of ketone bodies into the brain increases [9][10][11].…”
mentioning
confidence: 99%
“…Local PVN injection of α1-or α2-adrenergic receptor agonists suppressed pulsatile LH release in female rats [10]. Lipoprivic suppression of LH pulses is rescued by pretreatment with α1-or α2-adrenergic receptor antagonists in the PVN [25]. Thus, PVN α1-or α2-adrenergic receptor may be associated with the suppressed gonadotropin release under decreased energy availability.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous studies have indicated that the brain energy sensor resides within the hypothalamus and brainstem [18][19][20][21][22][23]. Previous studies have raised the possibility that brainstem energy sensors sense glucose and fatty acid availability to regulate gonadotropin secretion because administration of 2-deoxyglucose (2DG), a competitive inhibitor of glucose oxidation, or mercaptoacetate (MA), an inhibitor of fatty acid oxidation, into the fourth cerebroventricle (4V) suppresses LH pulses in rats [12,24,25]. Likewise, blockade of hindbrain monocarboxylate transporter 1 (MCT1), a ketone body transporter located in ependymocytes around the 4V, results in normalization of diabetic hyperphagia in rats [26].…”
mentioning
confidence: 99%
See 2 more Smart Citations